Teaching Ethnographic Methods for Cultural Anthropology: Current Practices and Needed Innovation. (2022) - Ruth, Alissa; Mayfour, Katherine; Sangaramoorthy, Thurka; Brayboy, Bryan McKinley Jones; Beresford, Melissa; Brewis, Alexandra; Bernard, H. Russell; Glegziabher, Meskerem Z.; Hardin, Jessica; Harper, Krista; Mahdavi, Pardis; Snodgrass, Jeffrey G.; et al.
No abstract available